Comparison of Hand Hygiene Attitudes and Hand Swab Cultures in the Mothers of Children with Heart Disease Before and After Cardiac Surgery - Karaağaç, Aysu Türkmen (Journal of Child Science, 2017)
Nosocomial infections (NI) carry high risk of morbidity and mortality especially for children undergoing surgeries. Hand hygiene (HH) is the most effective and economic measure of NI control. This study was designed to compare the HH practices (HHPs), maternal anxiety scores (MASs), and hand swab cultures (HSCs) in the mothers of children with heart disease before and after cardiovascular surgery (CVS) to determine the factors that raised maternal HH sensitivity for prevention of NI. This prospective study included 120 mothers (age: 20–45 years; mean: 31.6 ± 5.6 years), whose children underwent CVS in the Kartal Koşuyolu Research and Training Hospital, University of Health Sciences between November 2016 and February 2017. HHP of each mother was assessed by a questionnaire, 10 questions in two parts and HH score (HHS) was acquired. Then, HSC was obtained. Beck anxiety inventory was applied to determine MAS. The relations among demographic characteristics, MAS, HSC results, and pre-/postoperative HHS of the mothers were compared statistically. There was a significant increase in the HHS of the mothers in the postoperative period. Cronbach's a coefficient of the questionnaire was 0.84. Maternal HHS was significantly correlated with maternal age (p = 0.001), education (p = 0.002), and MAS (p = 0.001), but not with the income (p = 0.2). Moreover, one mother in the postoperative period (0.8%) versus five mothers in the preoperative (4.2%) had positive HSC. High education level, advanced age, and severe anxiety experienced by the mothers in their children's perioperative period were found to be the main factors that have raised maternal HHS, thereby resulting in better HSC results.
Keywords: cardiovascular surgery; children; hand hygiene; heart disease; mother; swab culture